2019
DOI: 10.17759/chp.2019150308
|View full text |Cite
|
Sign up to set email alerts
|

Religious Group Identification and Ethno-National Attitudes in Buddhist, Muslim and Orthodox Youth

Abstract: The current research studies the problems connected with interrelation between religiosity and intergroup hostility (or prejudice). We hypothesized and verified the connection between identification with religious group and ethno-national attitudes. Diagnostic methods measuring in-group religious identification, ethno-national attitudes, subjective categories of social consolidation and agreement with patriotic ideologems (by C.W. Leach, E. R. Agadullina, A.V. Lovakov, L. M. Drobizheva, O.E. Khukhlaev, N.V. Tk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…• Religious Group Identifi cation and Ethno-National Attitudes in Buddhist, Muslim and Orthodox Youth [25].…”
Section: Goals and Objectives Of The Association Of Psychology Assistmentioning
confidence: 99%
“…• Religious Group Identifi cation and Ethno-National Attitudes in Buddhist, Muslim and Orthodox Youth [25].…”
Section: Goals and Objectives Of The Association Of Psychology Assistmentioning
confidence: 99%
“…In recent years, various studies on migrants' children adaptation have been conducted. Konstantinov (2017) presented some research data based on the study of social and psychological adaptation of migrants to a new life environment (Khukhlaev et al, 2019;Konstantinov, 2017). El-Awad et al (2017) examined the mental health of juvenile refugees.…”
Section: Problem Statementmentioning
confidence: 99%
“…Based on the ethno-national attitudes definition and the results of its research in the context of intercultural relations [39,41,42,51,52], we can assume that Patriotic ethno-national attitudes will have a positive impact on the ICC development (i.e., ethno-relativistic orientation prevalence). Although Khukhlaev et al [39,41,42,52] showed a positive connection between Patriotic attitudes and above all with attitudes towards one's own group, Manoilova [52] found connection between a positive attitude to one's ethnic group and a positive attitude to other ethnic groups [51]. Based on these findings, we hypothesized that respect for native culture can be manifested in a broader context: as respect for the history, customs, and traditions of the mankind.…”
Section: Introductionmentioning
confidence: 99%